Pathological complete response rates with pertuzumab-based neoadjuvant chemotherapy in breast cancer: A single-center experience. (April 2020) - Matthews, Christina M; Nymberg, Kristen; Berger, Michael; Vargo, Craig A; Dempsey, Jessica; Li, Junan; Ramaswamy, Bhuvaneswari; Reinbolt, Raquel; Sardesai, Sagar; Wesolowski, Robert; Williams, Nicole; Lustberg, Maryam
Background: Pertuzumab-based neoadjuvant chemotherapy (NAC) has demonstrated successful pathologic complete response (pCR) rates when administered to patients with human epidermal growth factor receptor 2 (HER2)-positive, locally advanced breast cancer and has become standard of care. This study aimed to identify pCR rates in patients receiving a variety of pertuzumab-based NAC regimens. The effect of the addition of an anthracycline and impact of anthracycline and taxane sequencing on pCR was also assessed. Methods: A retrospective, single-center review was conducted on patients with operable, human epidermal growth factor receptor 2 (HER2)-positive breast cancer that received one of five pertuzumab-containing NAC regimens followed by definitive surgery. Results: Ninety-six patients were included in the analysis; overall, pCR was attained in 49 patients (51%). Of the 61 patients who received an anthracycline-containing NAC regimen, 30 (49%) attained a pCR. Of the 35 patients who received the non-anthracycline NAC regimen, 19 (54%) attained a pCR; difference in pCR was not statistically significant ( p = 0.63). Anthracycline/taxane sequence analysis showed that of the patients attaining pCR with an anthracycline-containing NAC, 77% of patients received the taxane portion upfront ( p = 0.17). Relative dose intensity of the anthracycline portion was similar irrespective of treatment sequence. However, relative dose intensity of the taxane portion was decreased with upfront anthracycline administration. Conclusion: These findings support current recommendations of adding pertuzumab to established regimens for treatment of locally advanced, HER2-positive, early stage breast cancer. The benefit of adding an anthracycline in the neoadjuvant setting remains unclear. Patients treated with the taxane portion of NAC upfront appeared to have a higher rate of pCR and better relative dose intensity than patients who received the anthracycline portion upfront, but differences were not statistically significant. These findings should be verified in a prospective clinical trial.